Virtual program in investigative skills within the framework of Faye Abdellah’s theory: Virtual program in investigative skills within the framework of Faye Abdellah’s theory - Espiritu Martinez, Antony Paul Espiritu Martinez (2024)
The main objective of the study was to evaluate the effectiveness of a virtual program aimed at improving research skills, based on the Theory of Faye Abdellah, applied to university nursing graduates in Tarma during the year 2022. The research used a quantitative methodology with a design quasi-experimental. The sample consisted of 40 graduates from the National University Daniel Alcides Carrión Branch – Tarma, distributed into two groups of 20 participants each: one control and the other experimental. For data collection, the interview technique was used and the instrument was a questionnaire. In the control group, the pretest analysis showed that 30% (6) of the graduates had unfavorable research skills, 65% (13) unfavorable and 5% (1) very unfavorable. In the post-test, 60% (12) continued to show unfavorable investigative skills and 40% (8) very unfavorable ones. On the other hand, the pretest of the experimental group indicated that 25% (5) of the graduates presented unfavorable research skills, 60% (12) unfavorable and 15% (3) very unfavorable. However, in the post-test, 85% (17) of the graduates in the experimental group showed very favorable research skills and 15% (3) showed favorable ones. In conclusion, a significant difference was observed between the groups. While the control group maintained unfavorable research skills, the experimental group, after the implementation of the virtual program, showed that 100% (20) of its graduates achieved research skills classified as very favorable or favorable (p = 0.001).